2016
DOI: 10.1002/jmri.25205
|View full text |Cite
|
Sign up to set email alerts
|

Breath‐hold MR measurements of fat fraction, T1, and T2* of water and fat in vertebral bone marrow

Abstract: Decaux, et al.. Breathhold MR measurements of fat fraction, T1 , and T2 * of water and fat in vertebral bone marrow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 25 publications
0
30
1
Order By: Relevance
“…The fat spectrum varies from organ to organ and a fat spectrum suitable to liver may not give accurate values for bone marrow. In several previous studies, the fat spectrum was modeled using the liver fat spectrum characterized by Hamilton et al and only the three main peaks (0.9, 1.3, and 2–2.2 ppm) were considered . In our work, the presence of multiple peaks in the fat spectrum was considered using a precalibrated fat spectrum characterized in the red bone marrow .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The fat spectrum varies from organ to organ and a fat spectrum suitable to liver may not give accurate values for bone marrow. In several previous studies, the fat spectrum was modeled using the liver fat spectrum characterized by Hamilton et al and only the three main peaks (0.9, 1.3, and 2–2.2 ppm) were considered . In our work, the presence of multiple peaks in the fat spectrum was considered using a precalibrated fat spectrum characterized in the red bone marrow .…”
Section: Discussionmentioning
confidence: 98%
“…The majority of CSE imaging that correct for T 2 * decay to improve the accuracy of marrow fat quantification assume a common (single‐ T 2 *) for water and fat, which is valid for liver applications at relatively low fat content. However, water and fat signals have independent T 2 * that may influence estimation of fat content, particularly at regions of high fat content and short T 2 *, which can be frequently encountered in bone marrow . In liver fat quantification, a single‐ T 2 * correction was chosen because of the advantage of a range of clinically relevant signal‐to‐noise ratios and water/fat ratios at low fat concentrations compared to dual‐ T 2 * correction .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, approaches with a single T 2 * correction or with a T 2 ′ correction (where T 2 ′ denotes the reversible spin dephasing relaxation constant) with a priori known water T 2 have been used. A dual T 2 * correction might be not severely affected by noise effects, when the fat quantification is performed not on a voxel‐by‐voxel basis but on a region of interest (ROI) level . After correcting all confounding effects, a good agreement has been reported in vivo between MRS‐based and imaging‐based PDFF in both the proximal femur and spine …”
Section: Technical Aspects Of Quantitative Bone Marrow Mri and Mrsmentioning
confidence: 99%
“…8 The fat-fraction of muscle tissue is not only relevant for the assessment of neuromuscular diseases, but is also utilized for investigations of other diseases such as lower back pain 9,10 as well as traumatic neck pain. 11,12 Approaches for segmentation so far make use of unsupervised techniques, such as active contours, 13 clustering, 14,15 random walks, 16,17 or atlas approaches. 18,19 It was shown that approaches for segmenting healthy muscle tissue in general do not perform well on pathological tissue.…”
mentioning
confidence: 99%